A restriction enzyme from Fusobacterium nucleatum 4H which recognizes GCNGC. - Leung, D W (1979)
A site-specific restriction endonuclease Fnu4H I isolated from Fusobacterium nucleatum 4H recognizes the DNA nucleotide sequence 5'G C N G C-3'/3'-C G N C G-5' and cleaves as indicated by the arrows.